Emergência e resolução de conflitos e/ou assédio moral na administração pública e seus impactos na saúde mental dos servidores - Almeida, Ivete Politano de (Universidade Federal de São Carlos, 2018)
The objective of this study was to analise the research already done on the emergence of interpersonal conflicts and / or moral harassment in the public administration and the impacts on the mental health of the employees, based on the theoretical contributions to the understanding of the causes and consequences of the conflicts and bullying at work, as well as possible approaches to prevent and combat the occurrence of phenomenon. The methodology adopted was the integrative review of the literature, with a temporal cut from 2007 to 2017; the data collection was done in the databases CAPES, SciELO-Br and SPELL, resulting in eight articles for analysis. Results were presented in three steps: construction of charts which allowed us to describe the data; detailed description of the information contained in the tables, distributed in six topics; grouping of articles into three categories: pleasure and suffering at work; moral harassment at work; stress at work. It was possible to identify in the public service the occurrence of interpersonal conflicts and practices of moral harassment in the work, due to the new forms of work organization of the capitalist model of production, mainly by the abusive practice of power relations, with consequences for mental health and life private use of servers, for public organizations and for society.
Keywords: Conflitos interpessoais; Assédio moral no trabalho; Sofrimento no trabalho; Saúde mental; Servidor público; Interpersonal conflicts; Moral harassment at work; Suffering at work; Mental health; Public server; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS